Teaching pronounciation skills for seventh-grade students using “Inside Out” movie - Prabantari, Adinda; Hidayati, Ratri Nur (International Journal on Education Insight, 2024)
Pronunciation plays a vital role in English as it directly impacts comprehension during communication. Watching movies can indeed be an alternative medium for improving pronunciation skills. Movies often feature numerous conversations between actors or characters, making it easier to comprehend spoken pronunciation. Moreover, movies can contribute to the practice of proper intonation in real-life contexts by observing how actors or characters pronounce words in different situations, enabling learners to enhance their pronunciation skills and refine their articulation of sounds and vowels. This research aims to find out whether ‘Inside Out’ movie is effective to teach students pronunciation. This type of research is quantitative research with a quasi-experimental research approach. The instruments used for this study were pre-test and post-test with a sample of 60 seventh-grade students at SMP Negeri 1 Imogiri Bantul. The pre-test and post-test were carried out to measure whether there was an effect before and after being given treatment. To analyze the data, the researcher used IBM SPSS 22. The study showed that watching ‘Inside Out’ movie is considered effective for teaching pronunciation because the significance value of the paired sample test experimental class showed 0.006, where if the result < 0.05 Ha is accepted while H0 is rejected.